On the predictability of a heavy rainfall event with dual rainbands - Lai, Qiaozhen; Zhang, Wei; Feng, Jinqing (Frontiers in Earth Science, 2023)
An extremely heavy rainfall with dual rainbands occurred in the Fujian province on May 22, 2014, causing severe disasters in Fujian. In order to investigate the key forecasting factors and the predictability of this case, the evaluation and sensitivity analysis of precipitation forecasts by the ensemble prediction system which is based on the European Centre for Medium-Range Weather Forecasts (ECMWF) global Model are carried out. The result show that the ECMWF-EPS have better ability to capture the intensity and spatial distribution of the northern rainband, but significantly underestimated the precipitation in the warm area. Through ensemble forecast sensitivity analysis and comparison between good and poor members, the main factors causing forecast deviations in the two rainbands and affecting the predictability of heavy rainfall were revealed. The forecast of rainfall distribution and intensity in the northern rainband was highly sensitive to the predictability of the weather-scale shear line. The westward bias in the forecasted position and the weakened intensity of the shear line were the main causes of the westward and weaker forecast of heavy precipitation in the northern region. Additionally, the forecast of 850hPa low-level jets, especially the forecasted intensity of zonal winds, which were closely related to the shear line, significantly influenced the intensity forecast of precipitation in the northern region. The forecast of precipitation in the southern warm area, which was far from the shear line, was more sensitive to the wind speed and thermodynamic conditions of the southwestern airflow in the boundary layer of the upstream inflow region. Most ensemble forecast members underestimated the intensity of the southwestern airflow in the coastal boundary layer of South China, which was the main reason for the near omission of heavy rainfall in the southern warm area. This study provides a quantitative correlation between low-level southwest jets along the coast of Guangdong and Fujian and non-typhoon heavy rainfall in Fujian, and explores their impact on heavy precipitation forecasts.